Investigation of carbonic anhidrase 1 (ca 1) and malic enzyme (me) in acıpayam sheep by using starch gel electrophoresis - Ümmühan Özdemir; Mehmet Nizamlıoğlu (Eurasian Journal of Veterinary Sciences)
Aim: For the determination of genetic structure of Acipayam Sheep, two enzyme loci were studied by using starch gel electrophoresis; carbonic anhidrase 1 (CA 1) and malic enzyme (ME).